(untitled) (Research, Society and Development, 2022)
Introduction: The growing population and urban expansion had as its main consequence, an exponential growth in the use of natural resources, and along with the increase in this consumption, comes the increase in the generation of Urban Solid Waste (USW), and inadequate disposal, being a very serious damage to the environment, aggravating the country’s socioeconomic situation in several ways. Objective: We sought to present a mapping of the Solid Waste Plans (SWP) used in the central cities of each Metropolitan Region in Paraíba, within the legal context, identifying the typology of plan, the form and time of management adopted by each municipality surveyed. Method: The documentary study, with an exploratory and descriptive approach, took place in 2022 in the central cities of the 12 metropolitan regions of the state of Paraíba. Data were collected by consulting the official websites of each central city, solid waste plans, legislation and administrative documents, in addition, a structured questionnaire was applied electronically to the bodies responsible for waste management. solids, in order to obtain information about the type of plan, form of management and implementation time. Results: The results showed that since the enactment of the National Solid Waste Policy (NSWP) there are still central cities without the construction of a SWP. Conclusion: The research found that there are advances in most of the municipalities surveyed, but there is a need for some municipalities to improve their management policies, since it is up to the local government to prepare municipal solid waste plans, individually or in partnership with other municipalities, through solutions consortium.